The Role of Bhabinkamtibmas In Problem Solving of the Community In the Jurisdiction of the Gorontalo Police - Joshua Mawitjere (Advances in Police Science Research Journal, 2021)
The role of bhabinkamtibmas in solving problems of the community in the jurisdiction of the Gorontalo Police. The purpose of this research is to describe and analyze the efforts of the bhabinkamtibmas role, and the factors that influence the role of bhabinkamtibmas in the implementation of problem solving in society. Sources of data in this study were members of the Polres, members of Polsek and members of the Gorontalo community, with a total of seven interview sources consisting of three Polres members, three Polsek members and one community member. In this study, namely the role of bhabinkamtibmas, and the factors that influence it. This research was conducted using a qualitative approach, with data collection techniques for observation, interviews, and document checking. The data analysis technique used includes data reduction, data presentation and drawing conclusions. The results of this study indicate that based on interviews with the Head of Binmas and Bhabinkamtibmas, the role of bhabinkamtibmas is carried out by the police unit starting from planning activities to reporting, which in practice assesses the role of bhabinkamtibmas used in accordance with the stages of management functions, namely planning, organizing, personnel placement, directing, and supervision. From the aspect of personnel capabilities, it is known that there is an assessment center stage and there has been no training effort for bhabinkamtibmas officers, so the officers do not have the required technical competence. Factors that support the role of bhabinkamtibmas include aspects of duty, productivity, motivation, evaluation, supervision and work environment. While the inhibiting factors are time, work environment and completeness of facilities. Therefore, optimization efforts are needed using the Bhabinkamtibmas Controlling application.